2015
DOI: 10.1073/pnas.1511701112
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical role of transferrin receptor 1 is essential for intestinal homeostasis

Abstract: Transferrin receptor 1 (Tfr1) facilitates cellular iron uptake through receptor-mediated endocytosis of iron-loaded transferrin. It is expressed in the intestinal epithelium but not involved in dietary iron absorption. To investigate its role, we inactivated the Tfr1 gene selectively in murine intestinal epithelial cells. The mutant mice had severe disruption of the epithelial barrier and early death. There was impaired proliferation of intestinal epithelial cell progenitors, aberrant lipid handling, increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 43 publications
2
63
0
Order By: Relevance
“…Genetic deletion of TFR1 is embryonic lethal (62). Tissue-specific knockouts showed that TFR1 is required for normal iron metabolism in skeletal muscle (63) and cardiomyocytes (64) and that TFR1 serves an unidentified iron-independent function in intestinal epithelial cells (65). Transferrin receptor 2, largely restricted to the liver and erythroid precursors (66), also interacts with holotransferrin but does not substantially contribute to iron uptake (67), acting primarily as sensor of systemic iron status (41).…”
Section: Transferrin and Transferrin Receptorsmentioning
confidence: 99%
“…Genetic deletion of TFR1 is embryonic lethal (62). Tissue-specific knockouts showed that TFR1 is required for normal iron metabolism in skeletal muscle (63) and cardiomyocytes (64) and that TFR1 serves an unidentified iron-independent function in intestinal epithelial cells (65). Transferrin receptor 2, largely restricted to the liver and erythroid precursors (66), also interacts with holotransferrin but does not substantially contribute to iron uptake (67), acting primarily as sensor of systemic iron status (41).…”
Section: Transferrin and Transferrin Receptorsmentioning
confidence: 99%
“…Establishing the mechanisms for noncanonical receptor signaling is of interest across kingdoms because noncanonical signal transduction has been observed in other signal transduction pathways of animals and bacteria (Federle and Bassler, 2003;Jenkins, 2009;Miller and McCrea, 2010;Chen et al, 2015). To understand the mechanism for the contrasting roles of ETR1 and ETR2 in germination, we determined that these receptors are predominantly affecting ABA signaling to alter germination in response to many stresses.…”
mentioning
confidence: 99%
“…Transferrin receptor 1 (TFR1) is known to be required for iron uptake by some, but not all, cell types (3)(4)(5)(6)(7). Its ligand, transferrin (TF), carries extracellular iron.…”
mentioning
confidence: 99%